Antioxidant capacity and protective role of methanolic extracts of jatropha platyphylla against oxidative stress on macrophage cells - DULCE L. AMBRIZ-PÉREZ; ROSALIO RAMOS-PAYÁN; MIGUEL A. ANGULO-ESCALANTE; JOSEFINA LEÓN-FÉLIX; FRANCISCO DELGADO-VARGAS; J. BASILIO HEREDIA (International Journal of Pharma and Bio Sciences, 2017)
Jatropha platyphylla is an endemic non-toxic Mexican specie from the Pacific coast, with high nutritional value and bioactive potential. The phenolics, tannins and antioxidant capacity of J. platyphylla methanolic extracts and their effect on oxidative stress in macrophages were determined. The antioxidant potential of total phenolic extracts (TPE) and free tannin extracts (FTE) were evaluated on macrophage cells. The total phenolic content ranged from 487.82-1753.89 mg GAE 100 g-1, with the highest proportion of hydrolysable tannins (452.73-904.01 mg GAE 100 g-1). In vitro chemical methods showed values of 29-87% inhibition of radical DPPH and 68-844 mmolTEg-1 for ORAC, and both methods revealed the influence of tannins content on antioxidant capacity. Besides, the TPE of bound phenolics from kernel and free phenolic from pulp showed 46 and 42% ROS inhibition, respectively. J. platyphylla tannins showed a high antioxidant capacity, while TPE from kernel and phenolics from pulp showed a protective role of oxidative stress on macrophages cells.